The Third-Worldism in the Argentinian Intellectual Field: A Hegemonic Sensibility (1961-1987) - Alburquerque, G (UNIV FED FLUMINENSE, DEPT HISTORIA, 2013)
This article studies the trajectory of the Third World and third-worldism in Argentina and tries to explain how its sensibility occupied a decisive place in the Argentinian intellectual field in the 1960s and 1970s. With this purpose, the disciplines, political tendencies, and cultural movements that put the Third World between their main worries were reviewed.